Craniosynostosis: a review of 143 surgically-treated cases - Çolak, Ahmet; Tahta, Kadir; Bertan, Vural; Erbengi, Aykut; Sağlam, Süleyman; Gürçay, Özdemir; Özgen, Tuncalp; Benli, Kemal; Özcan, Osman Ekin (The Turkish Journal of Pediatrics, 1992)
In this study, 143 cases of craniosynostosis are presented. There were 109 males and 34 females. The major complaints were skull deformity (92 patients), proptosis (38 patients) and microcephalus (32 patients). Neurological examination revealed the presence of optic atrophy in 24 patients and papilledema in 20 patients. Seventy-four patients (53%) had three or more suture closures, with the sagittal suture being the most commonly involved (20% of patients). All patients underwent surgery. Suture removal was performed in 131 patients (91.7%), suture removal plus orbital decompression in 34 (23.8%), and linear craniectomy plus wrapping in 12 (8.3%). The reoperation rate was 6.2 percent. During the follow-up period, preoperative papilledema and proptosis improved in 88.2 and 78.9 percent of patients, respectively. Skull deformity disappeared in 46.9 percent of patients, but remained unchanged in 16.6 percent.